2023
DOI: 10.1186/s12936-023-04501-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of optimal uptake of intermittent preventive treatment of malaria in pregnancy using sulfadoxine-pyrimethamine and outcome of pregnancy in selected health facilities: a cross-sectional study in Northern Ghana

Abstract: Background Ghana adopted the 2012 World Health Organization (WHO) policy on intermittent preventive treatment of malaria in pregnancy (IPTp) and implemented it in 2014 in all regions of Ghana. Despite the implementation of this policy, there has been an unacceptably low percentage of eligible women receiving the optimal dose of IPTp in Ghana which leaves millions of pregnant women unprotected from malaria. The study, therefore, assessed the predictors of three or more doses (optimal dose) of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…The findings also resonate with those conducted in Tanzania, which reported that ≥ 4 ANC visits were statistically associated with 3 or more doses of IPTp-SP [32]. Similarly, 4 or more ANC visits were a significant predictor of 3 or more doses of IPTp-SP uptake, as reported in a study in northern Ghana [41]. This reflection may be explained by the fact that regular ANC visits among these pregnant women frequently expose them to health educational information on IPTp-SP by health providers, and this may go a long way in influencing their decision-making during pregnancy.…”
Section: Factors Predicting the Optimal Uptake Of Iptp-sp Among Pregn...supporting
confidence: 83%
See 3 more Smart Citations
“…The findings also resonate with those conducted in Tanzania, which reported that ≥ 4 ANC visits were statistically associated with 3 or more doses of IPTp-SP [32]. Similarly, 4 or more ANC visits were a significant predictor of 3 or more doses of IPTp-SP uptake, as reported in a study in northern Ghana [41]. This reflection may be explained by the fact that regular ANC visits among these pregnant women frequently expose them to health educational information on IPTp-SP by health providers, and this may go a long way in influencing their decision-making during pregnancy.…”
Section: Factors Predicting the Optimal Uptake Of Iptp-sp Among Pregn...supporting
confidence: 83%
“…This is because initiating ANC early increases the chances of pregnant women receiving more doses of IPTp-SP than those who initiate ANC late or in their 3 rd trimester. In Northern Ghana, Malaria and anaemia infection in pregnancy was 53% and 46% times less among pregnant women who received 3 or more doses of SP [41]. This finding supports the claim that an appropriate dose of SP is still helpful in reducing the risk of malaria during pregnancy and increasing the weight of the baby.…”
Section: Therapeutic Effectiveness Of Iptp-sp Among Pregnant Womensupporting
confidence: 67%
See 2 more Smart Citations